Studi Penempatan Sumur Resapan Berdasarkan Nilai Laju Infiltrasi, Kualitas Fisik Air dan Tekstur Tanah pada DAS Batang Kuranji Kota Padang - Muhammad Fadli; Rusli HAR (Departemen Teknik Pertambangan FT UNP, 2021)
Abstract. Population growth in Padang City in 2007-2017 has increased from 838,190 people to 927,168 people (BPS Kota Padang, 2018). With this increase, the need for land / shelter and water needs is also increasing. This has resulted in high development, both in the city center and in the eastern suburbs. In addition, there is also a change in land use functions from forest areas, agricultural land, water catchment areas and cultural heritage lands to residential areas dominated by houses and concrete roads covering the ground. So that the reduced protected areas that function as water catchment areas and sources of clean water. Then with the rainfall in Padang City which is quite high, namely 4,661 mm³ / year, it causes puddles of water every time it rains. Therefore, it is necessary to plan the placement of infiltration wells around the Batang Kuranji watershed based on the value of infiltration rate, water physical quality, and soil texture.The research was conducted at 29 points that spread throughout the Batang Kuranji watershed. The data obtained are primary data, namely data on the physical quality of water (pH, redox potential, conductivity, TDS, salinity, resistivity, DO) and coordinate data.Based on the infiltration data, the average value of infiltration is 0.045710 cm / minute which is included in zone VI / E which is classified as low (<0.1 cm / minute). After conducting research with statistical analysis, physical water quality, rock lithology conditions, ground water level, and land use in the Batang Kuranji watershed, the placement of infiltration wells spread across almost all parts of the Batang Kuranji watershed which is a residential area, public service facilities. , industrial areas and fields. The number of infiltration wells to be placed is 9 points.Keywords: Infiltration Well, Infiltration Rate, Physical Quality of Water, Lithology of Rocks, Land Use.